SOSIALISASI DAN PELATIHAN SENIOR ECONOMIC OFFICIAL MEETING DALAM MENINGKATKAN KEMAMPUAN SISWA - SISWI MELALUI TEKNIK NEGOSIASI DIPLOMASI PADA SISWA-SISWI SMA NEGERI 1 PADALARANG KABUPATEN BANDUNG BARAT - Windary, Shylvia; Priangani, Ade; Rakhasyi, Fadhilah Yazid; Razaqa, Faza Fadhillah (Universitas Mataram, 2025)
This community service program aimed to enhance students’ negotiation and diplomacy skills through a simulation of the Senior Economic Officials Meeting (SEOM) at SMAN 1 Padalarang, West Bandung Regency. The program was motivated by students’ limited understanding of diplomatic mechanisms and the fact that SEOM had not been widely recognized as a simulation-based learning medium for developing soft skills such as communication, collaboration, and problem-solving. The program sought to socialize the concept of international forum simulations, provide an understanding of ASEAN meetings, and improve students’ negotiation, public speaking, and English language skills through a participatory approach. The implementation involved three main methods: socialization sessions, mentoring, and facilitation, all designed to introduce students to ASEAN diplomatic forums, strengthen communication skills, and foster engagement with global issues. The results indicated a significant improvement in students’ confidence when speaking in public and presenting structured arguments. Negotiation skills also improved, as evidenced by the strategies applied during the simulation. Students’ understanding of ASEAN meeting mechanisms increased, particularly in negotiation and decision-making processes. Moreover, students demonstrated high enthusiasm, actively asking questions, engaging in discussions, and participating in the simulation. These findings confirm that simulation-based learning is effective in developing diplomatic literacy and 21st-century skills among high school students.